2017
DOI: 10.1186/s12885-017-3508-x
|View full text |Cite|
|
Sign up to set email alerts
|

Palliative external beam radiotherapy for the treatment of tumor bleeding in inoperable advanced gastric cancer

Abstract: BackgroundTo assess the outcomes and prognostic factors associated with palliative external beam radiotherapy (EBRT), administered to patients with advanced gastric cancer.MethodsForty-two patients with bleeding gastric tumors that received EBRT for palliation were analyzed. The response to EBRT was assessed by the palliation of tumor bleeding. Patients were classified as either responders, or non-responders to EBRT. The prognostic utility of clinical and dosimetric variables was examined in a multivariate log… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 19 publications
3
39
1
1
Order By: Relevance
“…The present study shows that the use of hemostatic radiotherapy is effective and provides excellent primary bleeding control, with an overall rate of 89%, varying from 80% to 100% depending on the site of bleeding. The rates by site are comparable with the bleeding control rates reported in other isolated series of palliative external beam radiotherapy (EBRT) for gastro-intestinal [9] , [10] , [11] , urinary tract [12] , respiratory tract [13] , and gynecological origin [14] . At the time of publication, our study is the first report on hemostatic RT which includes extremity and H&N sites.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The present study shows that the use of hemostatic radiotherapy is effective and provides excellent primary bleeding control, with an overall rate of 89%, varying from 80% to 100% depending on the site of bleeding. The rates by site are comparable with the bleeding control rates reported in other isolated series of palliative external beam radiotherapy (EBRT) for gastro-intestinal [9] , [10] , [11] , urinary tract [12] , respiratory tract [13] , and gynecological origin [14] . At the time of publication, our study is the first report on hemostatic RT which includes extremity and H&N sites.…”
Section: Discussionsupporting
confidence: 78%
“…Likewise, Tey et al [10] conducted a similar analysis and reported 80% bleeding control in 103 cases, defined as the interruption in blood transfusions or gastroscopy for hemostasis, but similarly no increase in response ratio with higher BED (>39 Gy 10 ) ( p = 0.78). Alternatively, Lee et al [11] performed a small analysis of 42 patients treated with palliative EBRT for tumor bleeding in inoperable advanced gastric cancer, reporting resolution of the bleeding in 69% of the cases, with a positive association between BED ≥ 36 Gy 10 and bleeding resolution ( p < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…There is substantial evidence that palliative radiotherapy (RT) is effective in the management of bleeding, with reported treatment response (i.e. that bleeding would stop or diminish) varying from 45% to 100% [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] . It is, however, not clear which RT schedule, with regard to fractionation and total dose, is most ‘optimal’ (with as less fractions and less toxicity for the patient and as much as possible effect on symptom control) to manage bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…pain or obstruction) and the aim to reduce tumour volume can influence the chosen fractionation and total dose. Therefore, RT schedules described in literature vary considerably between studies (total dose ranged from 5 to 76 Gray {Gy}, number of fractions ranged from 1 to 39), consisting of only a few randomized controlled trials (RCTs) that compared different RT schedules, mainly with limited numbers of patients [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [16] , [17] , [18] , [20] , [22] , [23] . Table 1 summarizes the main studies on palliative radiotherapy in the management of bleeding using external beam radiotherapy (randomized and retrospective studies including information with regard to bleeding of at least 30 patients) that provide information with regard to fractionation schemes used, the bleeding control rate and/or duration of bleeding control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation